Utilization of referral agencies by guidance counselors in the public secondary schools of Manila - Cantero, Leticia L. 1927- (s.n.], 1963)
This study determines the utilization of referral agencies by the guidance counselors to supplement guidance services in the public schools of Manila. This also investigates the extent to which guidance counselors have utilized referral agencies and how some referral agencies can be utilized to supplement the services of these schools.